Predation of Ophiodes fragilis (Squamata: Anguidae) by Cariama cristata (Cariamiformes: Cariamidae) - Marcelo Augusto Pereira Coelho Dias; Eduarda Melo de Abreu Vieira; Clodoaldo Lopes de Assis; Renato Neves Feio (Caldasia)
Reptiles can be on the diet of some bird species, and the glass lizard Ophiodes fragilis seems to be no exception. Although predation events are not easily recorded, in this work we document a new record of predation by C. cristata upon O. fragilis. The event occurredin November 2017 in the municipality of Viçosa, state of Minas Gerais, Brazil, and helps to fill a gap in trophic relationships between the lizard and its predators.